Flexible nanocomposite electrothermal films based on carbon nanotubes and waterborne polyurethane with high reliability, stretchability and low-temperature performance for wind turbine blade deicing. (July 2022) - Zheng, Bojun; Wang, Huatao; Wu, Xulei; Yang, Ketong; Yu, Yangtao; Cui, Hongxin; Gao, Feng; Qian, Kun; Yao, Hai; Li, Jing; Xu, Wanting; Gong, Xiaobo; et al.
Graphical abstract: Highlights: The CNTs reinforce the WPU matrix to 3.7 and 135 times on their tensile strength and Young's modulus. The CNT/WPU film can start at −35 °C and work with a fast-repeated temperature cycle of −20 °C -+30 °C. The packaged CNT/WPU film heaters can withstand 100, 000 times 240° bending with resistance fluctuation of 3.17 %. The repeated stretching of 2.0 % strain in the length direction had no impact on the film heaters' temperature distribution. The ice block even on a huge blade will drop down in 5 min with the heaters' power density of 1600 W/m 2 . Abstract: Since the "net-zero" goal was proposed, wind power has been developed rapidly in recent years. Due to its large-scale installations in cold regions, the icing of wind turbine blades is currently one of the main limitations for efficient operation. In response to this issue, a highly reliable, flexible, stretchable, and lightweight in-situ deicing heating system based on the CNT/WPU nanocomposite films was developed. The CNT/WPU thin films were fabricated by the roll-to-roll gap-coating and hot-pressing process leading to as-prepared CNT/WPU film heaters have so outstanding reliability that they can withstand 100, 000 times 240° bending with the resistance fluctuation of 3.17 %, and the repeated stretching of 2.0 % strain in the length direction without any impact on their temperature distribution, and even the weak impact with 10 % strain. The films may have promising potential applications in various curved surface heating with strict requirements on reliability in the future.